Twin Rotor MIMO System Control using Linear Quadratic Regulator with Simechanics - Fahmizal, Fahmizal (2021)
This paper presents a linear quadratic regulator (LQR) for controlling a twin rotor MIMO system (TRMS) with Simechanics simulation. TRMS is a nonlinear multivariable system that can test flight control algorithms. Due to its high nonlinearity, problems arise when controlling motor speed variations in the main rotor and tail rotor. Thus, LQR control is implemented, so that the interaction between the main rotor control and the tail rotor can be designed accordingly. For additional functionality, we add Nbar gain to reduce steady-state error. The results obtained have improved the system to be more stable and increase response time compared to PID control. Lastly, a demonstration of the effectiveness of the proposed approach is provided by the Matlab environment using Simechanics. Â© 2021 IEEE.